Different Structural Origins of the Enantioselectivity of Haloalkane Dehalogenases toward Linear β‐Haloalkanes: Open–Solvated versus Occluded–Desolvated Active Sites. (23rd March 2017) - Liskova, Veronika; Stepankova, Veronika; Bednar, David; Brezovsky, Jan; Prokop, Zbynek; Chaloupkova, Radka; Damborsky, Jiri
Abstract: The enzymatic enantiodiscrimination of linear β‐haloalkanes is difficult because the simple structures of the substrates prevent directional interactions. Herein we describe two distinct molecular mechanisms for the enantiodiscrimination of the β‐haloalkane 2‐bromopentane by haloalkane dehalogenases. Highly enantioselective DbjA has an open, solvent‐accessible active site, whereas the engineered enzyme DhaA31 has an occluded and less solvated cavity but shows similar enantioselectivity. The enantioselectivity of DhaA31 arises from steric hindrance imposed by two specific substitutions rather than hydration as in DbjA.